Characterization of the chemical reactivity and nephrotoxicity of N-acetyl-S-(1,2-dichlorovinyl)-L-cysteine sulfoxide, a potential reactive metabolite of trichloroethylene - Irving, Roy M. (2012)
N-Acetyl-S-(1,2-dichlorovinyl)-L-cysteine (NA-DCVC) has been detected in the urine of humans exposed to trichloroethylene and its related sulfoxide, N-acetyl-S-(1,2-dichlorovinyl)-L-cysteine sulfoxide (NA-DCVCS), has been detected as hemoglobin adducts in blood of rats dosed with S-(1,2-dichlorovinyl)-L-cysteine (DCVC) or S-(1,2-dichlorovinyl)-L-cysteine sulfoxide (DCVCS). Because the in vivo nephrotoxicity of NA-DCVCS was unknown, in this study, male Sprague-Dawley rats were dosed (i.p.) with 230 µmol/kg b.w. NA-DCVCS or its potential precursors, DCVCS or NA-DCVC. At 24 h post treatment, rats given NA-DCVC or NA-DCVCS exhibited kidney lesions and effects on renal function distinct from those caused by DCVCS. NA-DCVC and NA-DCVCS primarily affected the cortico-medullary proximal tubules (S(2)–S(3) segments) while DCVCS primarily affected the outer cortical proximal tubules (S(1)–S(2) segments). When NA-DCVCS or DCVCS was incubated with GSH in phosphate buffer pH 7.4 at 37°C, the corresponding glutathione conjugates were detected, but NA-DCVC was not reactive with GSH. Because NA-DCVCS exhibited a longer half-life than DCVCS and addition of rat liver cytosol enhanced GSH conjugate formation, catalysis of GSH conjugate formation by the liver could explain the lower toxicity of NA-DCVCS in comparison with DCVCS. Collectively, these results provide clear evidence that NA-DCVCS formation could play a significant role in DCVC, NA-DCVC, and trichloroethylene nephrotoxicity. They also suggest a role for hepatic metabolism in the mechanism of NA-DCVC nephrotoxicity.